Pendampingan Analisis Gizi dan Sosialisasi Sertifikasi Halal Produk Bekasam Di Desa Meranjat Ogan Ilir, Sumatera Selatan - Rinto, Rinto; Herpandi, Herpandi; Hanggita, Siti; Lestari, Susi; Ridhowati, Sherly; Lestari, Shanti Dwita; Pitayati, Puspa Ayu; Yunindyawati, Yunindyawati (Swadaya: Jurnal Pengabdian Masyarakat, 2024)
Purpose: The aim of this community service activity is to provide information on the importance of HALAL and the steps to obtain HALAL certification for UMKM. Apart from that, it also provides information on the importance of listing the nutritional composition on product labels as a communication medium between bekasam producers and consumers. Methodology: The method used is socialization of HALAL certification and assistance with nutritional analysis of bekasam. Results: The success of the activity can be measured through pretest and posttest parameters as well as the results of laboratory analysis, nutritional content of bekasam. All activities starting from preparation, socialization and nutritional analysis went well. Participants can understand halal certification material above 50%. Bekasam has nutritional content (chemical composition) in the form of protein (23.39%), fat (7.73%), minerals (11.07%), carbohydrates (1.37%), and water (56.44%).